WANPRESTASI AKIBAT FORCE MAJEURE DAN PEMBAYARAN KOMPENSASI SISA KONTRAK KERJA PADA KARYAWAN PKWT (STUDI KASUS PUTUSAN PENGADILAN HUBUNGAN INDUSTRIAL NOMOR 9 PDT.SUS-PHI/2020/PN BNA) - Julius Taufik; Gunardi Lie (Jurnal Hukum Adigama, 2021)
Justice and social welfare are manifestations of efforts to achieve state goals as mandated in the 1945 Constitution of the Republic of Indonesia. In the implementation of justice and social welfare, the role of the community is required. To achieve this goal, the employment sector is needed to make it happen. The problem in the research raised by the author is a default due to Force majeure as a result of the Government's efforts to overcome the Covid-19 Pandemic based on Law Number 13 of 2003 concerning Manpower and Law Number 11 of 2020 concerning Job Creation.